Comparative study of six pear cultivars in terms of their phenolic and vitamin C contents and antioxidant capacity - Sánchez, Andrea C. Galvis (2011)
The main phenolic compounds in six pear cultivars were identified and quantified using high-performance liquid chromatography/diode array detection (HPLC/DAD) and HPLC/electrospray ionisation mass spectrometry (HPLC/ESIMS). Major quantitative differences were found in the phenolic profiles. The peel contained higher concentrations of chlorogenic acid, flavonols and arbutin than the flesh, where only chlorogenic acid was detected. Total phenolics ranged from 1235 to 2005mgkg−1 in the peel and from 28 to 81mg k g−1 in the flesh. Ascorbic acid and dehydroascorbic acid were detected in the peel, whereas only dehydroascorbic acid was present in the flesh. The ranges of vitamin C content were from 116 to 228mg kg−1 in the peel and from 28 to 53mg kg−1 in the flesh. The antioxidant capacity was correlated with the content of chlorogenic acid (r = 0.46), while ascorbic acid made only a small contribution to the total antioxidant capacity of the fruit.